Implementasi Pengembangan Karakter di Sekolah Dasar - Armitasari, Armitasari (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
The purpose of this study was to describe the implementation of character education at SDN 026 Bulo Polewali Mandar and the obstacles faced by teachers in implementing character education at SDN 026 Bulo Polewali Mandar. This research is a qualitative descriptive study. Observations, interviews and documentation are used as data collection techniques. The main tools are researchers using interview guides and observation guides. The method of analysis of this research is data reduction, data representation and verification/inference. The results of this study indicate that the implementation of character education at SDN 026 Bulo Polewali Mandar can be seen from integration with self-development programs, integration with learning activities and character values developed by the school.